2004
DOI: 10.1116/1.1813450
|View full text |Cite
|
Sign up to set email alerts
|

High reflectance of reflective-type attenuated-phase-shifting masks for extreme ultraviolet lithography with high inspection contrast in deep ultraviolet regimes

Abstract: Phase-shifting masks are a vital resolution enhance technique that will be used in extreme ultraviolet (EUV) lithography beyond the 20 nm node. In this article, we demonstrate a structure for a reflective-type attenuated phase-shifting mask, which is based on a Fabry-Perot structure with common materials in EUV masks. The mask structure not only performs 180°phase shift with high reflectance at EUV wavelength, but also has high inspection contrast at deep ultraviolet (DUV) wavelength. The top layer of mask str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…10 Soon after that Obert Wood et al from Lucent reported the first experimental realization of attPSM for EUV including extensive simulation studies. 11 Since then, many different forms of attPSM for EUV including etched multilayer configurations [12][13][14] and various absorber stack configurations [15][16][17] were proposed and investigated.…”
Section: Introductionmentioning
confidence: 99%
“…10 Soon after that Obert Wood et al from Lucent reported the first experimental realization of attPSM for EUV including extensive simulation studies. 11 Since then, many different forms of attPSM for EUV including etched multilayer configurations [12][13][14] and various absorber stack configurations [15][16][17] were proposed and investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various materials such as TaN, TaBN, TaSiN, Al 2 O 3 , Cr, and ITO have been studied as high-absorbance materials [7][8][9][10][11][12][13]. Further reduction in the thickness of the absorber layer, to prevent the geometric shadow effect in the exposure step, is challenging [14,15]. Hence, it is essential to develop new mask materials with low thickness and high optical contrast for use in circuit printing and defect inspection.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is reported that the lithography performance of an EUVL mask depends on the thickness of absorber materials because it is directly related to the imaging contrast, shadowing effect, focus shift effect, and thermal effect [2]. Therefore, the development of novel mask materials with high absorption at EUV is important for an actinic inspection of the mask and a high numerical aperture (NA) optical system [3].…”
Section: Introductionmentioning
confidence: 99%